ELECTROKINETIC SUPERCONDUCTING ENERGY ACCUMULATOR FOR LOCAL ELECTRICAL GRIDS - N. I. Smolencev; S. A. Kondrin (Известия высших учебных заведений: Проблемы энергетики)
In this article the importance of using superconducting technologies in power industry together with SMART GRID based on the analysis of program documents and scientific works has been done, which will allow the maximum extent to solve its problems. The physical principles of contactless suspension and its application in the superconducting energy storage and other promising devices and appliances are examined. The perspective of a superconducting electrokinetic storage of electrical energy (SCESE-1) are offered. The topology of a multilevel electrical network in which the superconducting electrokinetic energy storage device SCESE-1 acts as a regulator of optimizing the energy flows in local power grids is proposed.